Robust design of PC/ABS filled with nano carbon black for electromagnetic shielding effectiveness and surface resistivity - Sriseubsai, Wipoo; Tippayakraisorn, Arsarin; Lim, Jun Wei (My University, 2020)
This study focuses on the electromagnetic interference shielding effectiveness (EMI SE), dissipation of electrostatic discharge (ESD), and surface resistivity of polymer blends between polycarbonate (PC) and acrylonitrile-butadiene-styrene (ABS) filled with carbon black powder (CBp) and carbon black masterbatch (CBm). The mixtures of PC/ABS/CB composites were prepared by the injection molding for the 4-mm thickness of the specimen. The D-optimal mixture design was applied in this experiment. The EMI SE was measured at the frequency of 800 and 900 MHz with a network analyzer, MIL-STD-285. The result showed that the EMI SE was increased when the amount of filler increased. The surface resistivity of the composites was determined according to the ASTM D257. It was found that the surface resistivity of the plastic with no additives was 1012 Ω/square. When the amount of fillers was added, the surface resistivity of plastic composites decreased to the range of 106-1011 Ω/square, which was suitable for the application without the electrostatic discharge. The optimization of multi-response showed using high amounts of PC and CB was the best mixture of this research.
Keywords: Carbon black; Dissipation of electrostatic discharge; Electromagnetic shielding effectiveness; PC/ABS; Surface resistivity